The effects of three different flocculants on the harvest of microalgae Chlorella vulgaris. (October 2018) - Mu, R M; Zhao, Y L; Bu, Q W; Wang, M X; Liu, D
Abstract: Today, the value of microalgae has been found and used, especially in the production of biodiesel. But there is one problem to be solved, it is the problem of microalgae harvesting. In order to study the flocculant most suitable for Chlorella, this paper compared the recovery effect of three types of flocculants on Chlorella vulgaris ( C . vulgaris ), in the same conditions of flocculation. In this study, the absorbance measured by UV spectrophotometer was used to indicate the concentration of C . vulgaris culture, so as to calculate the recovery rate. Compare recovery rate with different conditions. Such as flocculation time, concentration of flocculant, concentration and pH of C . vulgaris culture medium. The experimental results show that the recovery rate of polychloral chloride as a flocculant is the best, and it can reach more than 95%, only considering flocculation efficiency. Taking into account the environmental safety factors, calcium hydroxide as a flocculant for the collection of C . vulgaris is the best. But, the flocculation effect of calcium hydroxide is relatively weak, and the best flocculation effect at 0.9g/L is 86%.